Fatty Acid Composition of Some Medicago L. (Fabaceae) Species From Turkey - BAKOGLU†, A.; BAGCI*, E.; KOCAK‡, A.; YUCE, E. (Asian Journal of Chemistry, 2009)
The seed oils of five Medicago species (Medicago lupulina, Medicagosativa, M. minima var minima, M. rotata var. eliezeri, M. rigidula var.rigidula) (Fabaceae) were investigated for their fatty acid composition.The fatty acid composition of these five different species were determinedby gas chromatography of the methyl esters of their fatty acids.The seed oils of Medicago species contained palmitic acid (10.79-19.18 %),among the saturated acids with a small amount of stearic acid andarachidic acid. The major unsaturated fatty acids found in the seed oilswere linolenic acid (43.69-25.51 %) and linoleic acid (41.95-23.99 %).Unsaturated fatty acid concentrations of Medicago species were foundhigher than the saturated fatty acid concentration. The results showedthat Medicago patterns has linoleic-linolenic and oleic-palmitic typefatty acid. The result were discussed in means of renewable resourcesand chemotaxonomy.